Ethnobotanical study of traditional knowledge on plant used in traditional bath (mandi serom) among Malay midwives in Perak and Negeri Sembilan - Othman, Rashidi; Abdul Razak, Nur Illani; Ishak, Nooriszai (Medwell Journals, 2014)
This study analyzed the traditional knowledge of plants used in traditional bath which known as mandiserom in Malay culture. Mandiserom is an important traditional way in postpartum practice among Malay communities in Perak and Negeri Sembilan. The study was carried out through face to face interviews with Malay midwives as the respondents and collection and identification of the plants in the area. A total of 25 species of plants were noted and collected during the botanical surveys. Most of them are predominated by zingibers and herbaceous plants. In mandiserom, the plants are used to get rid the body odour for spiritual cleansing, for hygienic purposes and to ward off mystical forces known as makhlukhalus in Malay culture. Traditional beliefs and practices surrounding postpartum practice were highly prevalent among young women in Malay culture. However this traditional knowledge is seldom recorded and only passed down through generations. Therefore these new ethnobotanical records are a rich source towards preservation of traditional knowledge of plants that can be further up for clinical studies in Malaysia.